LYELL’S SYNDROME IN MEDICO-LEGAL AND PATHOLOGICAL-ANATOMICAL PRACTICE - L. N. Zimina; A. I. Ibraeva; G. V. Mikhailova; T. K. Osipenkova-Vichtomova; V. A. Strokova; V. V. Titova (Неотложная медицинская помощь, 2016)
We report 9 clinicopathologic cases of Lyell’s syndrome, known as toxic epidermal necrolysis (TEN). Five deceased patients had dermal exposure to cow parsnip, grey mercury ointment or whitening agents. In 4 cases, TEN developed in the course of drug treatment as a part of polytherapy, and in one of them it was accompanied with the infection. All of TEN patients suffered from acute or chronic diseases, endogenous or exogenous intoxication, immunodeficiency.